Experimenal study of a low wake wash catamaran leisure boat - Omar Yaakob, 1960-, author; Mohd. Afifi Abdul Mukti, author; Ahmad Nasirudin, author; Mohd. Arizam Abdul Wahap, author; International Conference on Marine Research and Transportation (2007: Italy) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL